Development of Instagram-Based Learning Media to Increase Learning Motivation of Tenth Grader in Economics Subjects at SMA Ar-Raudhah - Ratnasari, Lia Tri; Mariatun, Ika Lis; Arief, Zaiful (Journal of Educational Sciences, 2022)
Instagram social media has become a popular social media among students and in it’s use, of course, it must be balanced with its usefulness as used as a learning reference. This study aims to develop Instagram-based learning media in economics subjects and measure the level of student learning motivation towards learning media. The method used is Research and Development with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The results of this study are based on validators' assessment of Instagram-based learning media which obtained an average validity of 3.89 (material experts), 3.87 (media experts) and 4.49 (learning practitioners) so that they were declared valid and suitable for use. Meanwhile, the results of measurements on student learning motivation increased from the original score of 2415 to 2698 after the implementation of Instagram-based learning media and obtained a gain score of 0.5 which was interpreted to be in the moderate category. This shows that Instagram-based learning media is effective in increasing student learning motivation.